The role of the patent system in the internationalization of the technicalknowledge diffusion - Małgorzata Niklewicz-Pijaczyńska (Economic and Environmental Studies (E&ES), 2019)
The article attempts to show the role of the patent system in the internationalization of diffusion of technical knowledge. Its purpose is to analyse, use of international technical knowledge made available through patent systems, by Polish companies that are inventively active. For its implementation, research was carried out based on a qualitative analysis of the so-called patent citations, included in the technical documentation submitted for the protection of inventions. Conclusions resulting from the research show a high degree of internationalization of the diffusion of technical knowledge in relation to scientific and technical publications and low when the existing technical solutions are the basis.
Keywords: O3; O33; O34; Q55; 330; knowledge diffusion; innovations; patents; patent citations